Effects of Nutrient Salts on Growth Performance of Oocystis borgii - Bin ZHANG; Yuanyou LIN; Baolong YUAN; Xien ZHU; Tiancong CHEN; Yongzhen ZHAO; Naikun SHEN (Guangdong nongye kexue)
【Objective】The effects of nitrogen, phosphorus, carbon and iron nutrients on the growth of Oocystis borgei were explored, and the optimal nutrient formula was selected to provide references for its efficient and large-scale cultivation.【Method】Single factor test was used to analyze the effects of different nitrogen, phosphorus, carbon and iron nutrients on the growth of O. borgei, to obtain the best nutrients and their respective concentrations. Orthogonal tests were conducted to optimize the factors that had a great impact on the the growth of O. borgei. Finally, the optimal nutrient formula was obtained.【Result】The results of the single factor test showed that the optimal sources and concentrations of nitrogen, phosphorus, carbon and iron sources for O. borgei were CO(NH2)2 160 mg/L, C3H7Na2O6P 8 mg/L, NaHCO3 1 g/L, and FeCl3 0.2 mg/L, respectively. The results of the orthogonal tests showed that the effect of each nutrient on the growth of O. borgei ranked as: phosphorus source > nitrogen source > carbon source, and phosphorus source had the most significant effect on the growth of O. borgei (P < 0.05). The optimal formula was: CO(NH2)2 120 mg/L, C3H7Na2O6P 12 mg/L and NaHCO3 2.5 g/L. Under the optimal condition, the algal cell density reached 22.07×106 cells/mL, which was 12 times higher than that before optimization (1.74×106 cells/mL).【Conclusion】The optimal nitrogen, phosphorus, carbon, and iron sources and concentrations for O. borgei were determined and the optimal nutrient formula was obtained by optimizing the conditions, which significantly increased the algal cell density.